Smart Hi-Tech Ring / Nurul Najwa Ghani … [et al.] - Ghani, Nurul Najwa; Mohd Rosli, Nabilla Affiqqah; Sobri, Siti Rubaani (2020)
Smart Hi-Tech Ring product from our company is a not a completely a new product but an existing product that has undergone significant improvement and be upgrade from time to time by using apps which is connect to tech ring. It is a biometric based wearable ring that can make your daily life easy because all with a wave of one magic finger uses of combination of fingerprinting which is have a finger print sensor at the base of the ring and an optical proximity sensor to ensure that a user's credentials can't be accessed by a third party. This Smart Hi-Tech Ring used together with apps which is available for iOS and Android. Smart Hi-Tech Ring presents the mobile app with just a touch of a thumb. It provides 'beep sound' or vibration feedback for each notification or alert that comes from your mobile phone.